Renal Protective Effects of N-Acetyl-Seryl-Aspartyl-Lysyl-Proline (Ac-SDKP) in Obese Rats on a High-Salt Diet. (2nd May 2018) - Maheshwari, Mani; Romero, Cesar A; Monu, Sumit R; Kumar, Nitin; Liao, Tang-Dong; Peterson, Edward L; Carretero, Oscar A
Abstract: BACKGROUND: Obesity is a public health problem, associated with salt sensitive hypertension, kidney inflammation, and fibrosis. N -acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a tetra peptide with anti-inflammatory and anti-fibrotic properties. However, its effect on preventing kidney damage in obesity is unknown. We hypothesized that Zucker obese (ZO) rats on a high-salt (HS) diet develop renal damage, inflammation, fibrosis, and this is prevented with Ac-SDKP treatment. METHODS: Zucker lean (ZL) and ZO rats (8 weeks old) were treated with Ac-SDKP (1.6 mg/kg/day) while maintained on either a normal-salt (NS; 0.4%) or HS (4%) diet for 8 weeks. Systolic blood pressure (SBP), albuminuria, renal inflammation, and fibrosis were evaluated. RESULTS: HS diet increased macrophage infiltration in the kidneys of both ZL and ZO rats but was significantly higher in ZO rats receiving the HS diet (ZL + NS, 13.9 ± 1.3 vs. ZL + HS, 19.14 ± 1.5 and ZO + NS, 25.5 ± 1.4 vs. ZO + HS, 87.8 ± 10.8 cells/mm 2 ; P < 0.05). Ac-SDKP prevented macrophage infiltration in ZO rats (ZO + HS + Ac-SDKP, 32.18 ± 2.4 cells/mm 2 ; P < 0.05). Similarly, glomerulosclerosis, cortical, and medullary interstitial fibrosis were increased in ZO rats fed the HS diet, and Ac-SDKP attenuated these alterations ( P < 0.05). SBP was increased in ZO rats fed the HS diet (ZO + NS, 121.3 ± 8.9 vs. ZO + HS, 164 ± 6.9 mm Hg; P < 0.05), and it was significantly decreased with Ac-SDKP treatment (ZO + HS + Ac-SDKP, 144.05 ± 14.1 mm Hg; P = 0.004). Albuminuria was higher in ZO rats than in ZL rats; however, neither HS nor Ac-SDKP treatment affected it. CONCLUSIONS: Ac-SDKP treatment in ZO rats fed a HS diet prevented renal damage by reducing inflammation, fibrosis, and SBP.